2013
DOI: 10.1038/bjc.2013.129
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cancer following primary total hip replacement or primary resurfacing arthroplasty of the hip: a retrospective cohort study in Scotland

Abstract: Background:Release and dispersion of particles arising from corrosion and wear of total hip arthroplasty (THA) components has raised concerns about a possible increased risk of cancer. Concerns have been heightened by a recent revival in the use of metal-on-metal (MoM) hip prostheses.Methods:From a linked database of hospital discharge, cancer registration, and mortality records, we selected a cohort of patients who underwent primary THA (1990–2009) or primary resurfacing arthroplasty (mainly 2000–2009) in Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 27 publications
9
46
0
Order By: Relevance
“…Since new generation MOM‐HR has been introduced to address the needs and expectations of young and active patients with long life expectancy, there is a concern about the unknown risks of long‐term exposure to metal ions and metal debris. Adverse effects of a chronic exposure to raised metal ion levels theoretically include chromosomal damage, teratology effects, and malignancy . Patients implanted with these prostheses still have a too short follow‐up to entirely rule out an increased risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since new generation MOM‐HR has been introduced to address the needs and expectations of young and active patients with long life expectancy, there is a concern about the unknown risks of long‐term exposure to metal ions and metal debris. Adverse effects of a chronic exposure to raised metal ion levels theoretically include chromosomal damage, teratology effects, and malignancy . Patients implanted with these prostheses still have a too short follow‐up to entirely rule out an increased risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, significantly increased chromosomal translocations in peripheral blood lymphocytes were observed in patients with Co Cr‐alloy implants, as well as chromosomal changes in bone marrow cells . On the contrary, several clinical studies, matching joint arthroplasty and cancer registries, reported no relationship between cancer and long lasting metal implants . Mäkelä et al in a population‐based study comparing patients with MOM total hip arthroplasty with patients who underwent conventional non‐MOM implants, reported an increased incidence of basal cell carcinoma in the MOM cohort compared with both normal population and the non‐MOM cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Using hospital discharge, cancer, and mortality records, Brewster et al (2013) studied the incidence of cancer in 1,317 metal-on-metal resurfacing arthroplasty patients in Scotland who were operated between 2000 and 2009. The risk of cancers overall (n = 39) was not increased (Brewster et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of melanoma was found to be increased in patients with a conventional hip implant inserted during 2005–2009 in Scotland (SIR = 1.4, CI: 1.1–1.9), but not in patients with a metal-on-metal hip resurfacing device (Brewster et al 2013). The incidence of melanoma in the non-metal-on-metal cohort in the current study was higher than in the Finnish general population, as also found in our previous report (Mäkelä et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a number of epidemiological studies have been conducted to assess the carcinogenic potential of CoCrMo MoM hip implants. Brewster et al (2013) reported a very modest increase in overall cancer risk among patients in Scotland with MoM hip replacements (Standardized Incidence Ratio 1.05, 95% confidence interval 1.04-1.07), but noted that this increased risk may reflect inadequate adjustment for confounders. They found that the incidence of cancer in patients with MoM hip implants was similar to that of the general Finnish population and no higher than patients with non-MoM implants; however, the authors caution that data with a longer follow-up time are needed to reach a more definitive conclusion about the cancer risk associated with MoM implants.…”
Section: Metallic Orthopedic Implantsmentioning
confidence: 99%